(untitled) (Balkan Journal of Applied Mathematics and Informatics, 2024)
In the digital age, securing smart touch devices is of paramount importance to safeguard sensitive information. Traditional graphical password systems, while convenient, remain vulnerable to attacks such as shoulder surfing and smudge tracing. This paper introduces a novel multi-action grid authentication system that enhances security while preserving ease of use. The system allows users to authenticate by performing two actions—tapping and replacing—within a 3x3 grid. Through iterative development and testing, the method shows significant improvements in preventing common security threats while maintaining high user satisfaction. A thorough analysis of password space is also conducted, demonstrating the system’s robust resistance to brute-force attacks. Our findings suggest that this multi-action approach offers a secure, efficient alternative to existing graphical password systems.